Analisa Tingkat Likuiditas dan Profitabilitas terhadap Harga Saham Perusahaan yang Terdaftar di LQ45 BEI Periode 2017-2019 - Windy Girmaliya; Dumadi; Yenny Ernitawati; Hilda Kumala Wulandari; Roni (Journal of Accounting and Finance (JACFIN), 2020)
The existence of a campaign about Yuk Saving stocks makes people have an understanding of stocks so that they are interested in investing in stocks. Stock prices are a benchmark for investors in investing. Many things can affect stock prices, so research is needed on the factors that affect stock prices. This study uses quantitative methods with panel data regression. The number or samples used are 33 public companies which are included in LQ45 shares. This study asseses financialperformance intheshort therm by using liquidity ratios and profiabilityratios. The liquidity ratio describes the company's abilityto payits financyal obligation that must be fulfiled imediately, measured using the currentratio. Profitaibility rasio is use to meausure the conpany's ability to generatiprofit, measure by using ROA. The company willfind ways to maximize the value of it shares indicated by its share price. The stock preceuse in this study is the closing price.